Katecheza maryjna dzieci i młodzieży szkolnej. Źródła, zakresy tematyczne, zasady - Tomasik, Piotr (Collectanea Theologica, 2019)
The aim of the article is to show the main challenges facing Polish catechesis, including religious education at school; these challenges relate to the proper approach to the person of the Mother of God in the experience and practice of Catholicism, to appreciate the element of evangelization and identity in the preaching of faith. The author addresses the issue of the relationship between three concepts as follows: catechesis, the school of faith and the school of Mary described in the Bible and through Tradition. Then, the proper approach to Mariology in the context of entire theology it synthetically shown. The summary is a presentation of the mystery of Mary as the content of catechesis and the formulation of postulates related to Marian catechesis.